Óleo essencial de alfavaca (Ocimum gratissimum L.) como aromatizante em bebidas alcoólicas formuladas - Costa, Joel Conceição (2016)
The Ocimum gratissimum L. is a plant rich in essential oils whose main constituents are thymol and eugenol and due to their antioxidant propertiesthey have been used for medicinal purposes, and also as flavorants, spice, fragrances, among others. Essential oilshave been used by the food industry successfully replacing the synthetic and artificial flavorants.Besides standardization close to ideal, it is also possible to have a final product with greater value in terms ofsalubrity in its production, i.e. a drink. This standardization is valued by the consumer because when buying the drink there is the expectation to find the same characteristics of flavor and aroma such as the natural. The objective of this study was to perform a sensory analysis in order to evaluatedifferent concentrations ofessential oil of Ocimum gratissimum L. as flavoringof an alcoholic beverage.The essential oil was obtained by extraction of fresh leaves of plants grown in the Garden of Medicinal Plants at the Department of Agriculture of the University of Lavras (DAG/UFLA), four harvests were made, the first 120 days after planting the seedlings and three more every 120 days. To obtain the drink it was added 2% crystallized sugar as syrup, mineral water to reduce the alcohol content to 30° GL and then added the essential oil of O. gratissimum in four different concentrations: 200, 300, 400 and 500 µL to 1000 mL of cachaça. Following the sensory analysis it was held an affective test by preference and acceptability of the drinks (acceptance test using hedonic scale). All concentrations tested were accepted. According to the acceptance index, the best aromatization occurred with the concentration of 300 µL L-1. Regarding flavor only the concentrations of 200 µL L-1 and 300 µL L-1 achievedthe acceptance rate (over 70%), considering the acceptable limit.